EFFICIENCY OF THE APPLICATION OF LIMESTONE SLUDGE AS AMELIORANT ON THE TURF-PODSOLIC SOILS OF THE WESTERN POLISS’A OF UKRAINE - Veremeіenko Serhii; Furmanets, Oleh; Pіddubnіak V.; Kondratіuk M. (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
In the article the data of research of influence of introduction of various doses of limestone sludge on decrease of acidity of turfpodzolic sandy soils is given. It was established that the use of limestone sludge positively influenced on the growth and development of corn plants. Already in the phase of 7 leaves on variants with using lime slime plants were higher by 5.6-18.5% comparing to control. In the phase of panicle ejection, the control variant had a height of 153.7 cm, whereas when using sludge, plant height was 214.3 cm (0.5 dose) to 237.3 cm (full dose + peat). The weight of the above-ground part of plants in variants with a melioration increased by 70.7-93.4%, and the root mass increased by 120.7-207.7%. The weight of the corncobs increased by 61.5-67.6%. Also the corn yield was increased in the experimental variants. At the yield of grain at the control variants at 3.79 tons / ha, the introduction of reclamation in doses of 0.5, 1.0, 1.5, 2.0 norms and 1.0 norm + peat increased the yield of maize to 6.22, 6, 68, 6,53, 6,34 and 6,54 t / ha respectively. Calculations also showed that at a price of limestone sludge in 6 UAH. for a ton and shoulders of delivery in 180 km the application of reclamation pays off already in the first year of growing corn for grain.